‘Velvet Triangles’ in Women, Peace and Security Agenda in Indonesia - Nur Azizah; Muhammad Ammar Hidayahtulloh; Lintang Cahya Perwita; Ali Maksum (Jurnal Hubungan Internasional, 2021)
Resolution 1325 on Women, Peace and Security (WPS Agenda) has been recognized as a landmark in the history of global efforts to maintain international peace and security by centering women on the agenda. Indonesia has shown its commitment to WPS Agenda by adopting its first National Action Plan (NAP) in 2014. On top of that, Indonesia is also committed to increasing the number of female peacekeepers in the UN peacekeeping missions. This research aims to examine how WPS Agenda as a global normative framework diffuses and is internalized in Indonesia. This research employed a feminist institutionalist approach and a qualitative method. Using the concept of ‘velvet triangles’ by Alison Woodward (2004) as our theoretical framework, we argue that the triangular network of velvet actors—consisting of feminist bureaucrats, civil society organizations’ activists, and gender experts—plays a critical role in making a considerably important space for the diffusion of WPS Agenda within Indonesia’s domestic politics and foreign policy debates. In concluding the article, we propose two considerations taking into account the formal and informal arrangement of the velvet constellation and the transnational scale of the network’s actors to provide a more nuanced conceptual definition of velvet triangles.